(untitled) (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Bousba R, Gueraiche S, Kanouni MR, Bounar R, Djekoune A, Khammar H, Nadia Y. 2020. Genotypic diversity assessment of some durum wheat (Triticum durum) genotypes using RAPD analysis. Biodiversitas 21: 2696-2701. Knowledge of genetic variability in durum wheat (Triticum durum Desf.) is of major importance in the development of breeding programs and the preservation of local landrace resources. The objective of this study is to highlight the molecular polymorphism among six durum wheat genotypes from different origins and characterized by different sensitivity to drought tolerance (tolerant, semi-tolerant, and non-tolerant). 15 Random Amplified Polymorphic DNA (RAPD) markers were used to assess the molecular diversity of these genotypes. Our results show a total of one hundred and sixty-nine amplicons, where one hundred and twenty-four are polymorphic bands. The number of bands per primer ranged from two (OPJ-06) to fifteen bands (primers OPE-13 and OPB-01). The values of the Allelic frequency varied from 1 (OPJ-06) to 0.20 (OPA-17) and 0.19 (OPE-13, OPO-06, B-19 and OPA-20). Also, the values of the coefficient of genetic similarity range from 0.69 to 0.80, these results indicate a large variation between tested genotypes. According to the dendrogram generated by the RAPD approach, we obtained four distinct groups: the first one (G1) contains GTADUR and KORIFFLA x SHAM, the second group (G2) contains the local genotype BIDI-17. However, the genotype WAHA was in the third group (G3), the fourth and fifth groups contained the genotypes CIRTA and TELL, respectively. A complementary analysis was done to estimate genetic differentiation, using CPA Analysis that indicated four groups among the six genotypes, where, the local genotypes BIDI-17 and CIRTA were classified together. For allele’s richness, the local genotypes show in this investigation, the highest values in comparison to the introduced genotypes, which suggested the performance of the RAPD markers (high polymorphism and fast genetic analysis). The molecular markers RAPD-PCR type, despite their non-specific characteristics, has shown a strong aptitude for genetic characterization in durum wheat and a high level of polymorphism, which makes it possible in a preliminary study to make exploitable discrimination. These results may be helpful in the improvement and varietal selection, and useful in accelerating breeding programs of durum wheat.